Determination of Hatching Performance, Yolk-Sac Absorption, and Larval Growth Rates in Abant Trout (Salmo trutta abanticus), Brook Trout (Salvelinus fontinalis), and their Hybrids - Sonay, FD; Kavuk, Z (Journal of the Hellenic Veterinary Medical Society, 2023)
In this study, hatching performance, yolk-sac absorption, and growth rates of Abant trout (Salmo trutta abanticus), brook trout (Salvelinus fontinalis), and their hybrids were investigated. In this contex, relationships between duration (days) and total larvae length, total larvae wet weight, dry larvae body weight and yolk-sac weights, and larval growth were determined. At the end of the study, eye pigmentation, hatching, and larval survival rates were defined as 99.50%, 97.68%, 98.97% for Abant trout, 87.35%, 68.97%, 71.54% for brook trout, 96.12%, 64.18%, 56.82% for S.t.a. ♀ x S.f. ♂ hybrid and for S.f. ♀ x S.t.a. ♂ hybrid 14.98%, 0.45%, respectively. The results indicated there were significant linear relationships between degree-day and length, total wet weight, dry body weight, and dry yolk-sac weight in Abant trout, brook trout, and their hybrids. This relationship has been demonstrated as decreasing in the yolk-sac and as increasing in others. As a result of crossing, it was observed that the hatching efficiency of hybrid (S.t.a.♀ x S.f.♂) was similar to brook trout, and growth performance was similar to Abant trout. The results will help further studies and will contribute to the management practices of the stocks of Abant trout, brook trout, and their hybrids.